Some Parents Survive and Some Don't: The Army and the Family as "Greedy Institutions". (20th February 2022) - Strader, Eiko; Smith, Margaret
Abstract: The military and the family are "greedy institutions" that require the full attention of their members. Being aware of the tension between work and family, the United States military has developed family support policies that are more generous than legally required to ensure personnel readiness. However, family formation remains a major obstacle for recruitment, retention, and integration of women. Using administrative data, this research shows that fathers were more likely to leave prematurely for family reasons than childless men, particularly among non‐Hispanic Black and American Indian/Alaska Native men. However, women who gave birth while in service were much less likely to leave for work–family reasons than childless women, while the same could not be said for women who joined as mothers and had no additional children. The results reflect the gendered logic of the organization and the narrow conceptualization of work–family conflict, both of which perpetuate gender‐role stereotypes.